Liberal Principles, Realist Actions: U.S. Foreign Assistance in the War in Ukraine - Sasongkojati, Hiu; Subono, Nur Iman (Journal of Strategic and Global Studies, 2023)
The 2022 Russian invasion of Ukraine has led to a concerted international effort, with the United States at the forefront, to provide assistance in the form of weaponry and logistical support to the embattled country. While no soldiers are deployed to the front line in an official capacity, the U.S. has provided aid through many security assistance programs dating back to 2014 without becoming an active participant in the conflict, drawing parallels between Ukrainian defense and American national interests in the process. There is a realist element to this approach by maximizing U.S. interests against Russia with minimal costs, but there is also a liberal element by the invocation of moral arguments in order to maintain voter approval to continue providing aid. The paper explores this hypothesis on the simultaneous, but distinctive, use of realist and liberal approaches in U.S. military aid to Ukraine by examining publicly available data on U.S. foreign assistance and survey results. The analysis contributes to a renewed understanding of U.S. foreign policy in the contemporary era and its response to national security threats without the immediate use of kinetic military action, in addition to furthering the literature on public opinion and foreign aid.